Biodegradable and conductive chitosan–graphene quantum dot nanocomposite microneedles for delivery of both small and large molecular weight therapeutics1. Issue 64 (12th July 2015) - Justin, Richard; Román, Sabiniano; Chen, Dexin; Tao, Ke; Geng, Xiangshuai; Grant, Richard T.; MacNeil, Sheila; Sun, Kang; Chen, Biqiong
<x xml:space="preserve">Abstract</x> Chitosan–graphene quantum dot nanocomposites are used in microneedle arrays for transdermal delivery of small and large molecular weight drugs.